Implementing One Stop Schooling System Program in Reaching Graduate Standards of Santri at Salaf Islamic Boarding Schools - Etharina Lathifah; M. Nurul Humaidi; Mohammad Kamaludin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The study aims to describe the application of the one-stop schooling system in achieving standards for graduating students in the Islamic Boarding School Al-Ma'had Setu Bekasi. The study uses field research with a qualitative descriptive research design, while data is collected by using interviews, observation, and document collection related to the research focus. Interview techniques are used to collect data from several sources, including the school's founders, management, and students. The analysis flow follows an interactive analysis model, with the process of analysis made through 4 stages data collection, data reduction, data presentation, and deduction. The findings suggest that the Pondok Pesantren Salaf Al-Ma'had Setu Bekasi uses the One Stop Schooling System to achieve the standard characters for graduating students; ten standards have been designed. Pondok Pesantren Salaf Al-Ma'had Setu Bekasi belongs to the traditional Islamic boarding school but uses modern teaching systems and methods. In the application of the One Stop Schooling System, a teaching and educational method becomes the primary facility for achieving the character standards for graduating students. In the program, there is also an organization that serves as a support facility to help students develop their insights, knowledge, talents, and skills.